Water Management on the U.S.-Mexico Border: Achieving Water Sustainability and Resilience through Cross-Border Cooperation. Issue 2 (4th March 2023) - Lara-Valencia, Francisco; Coronado, Irasema; Mumme, Stephen; Brown, Christopher; Ganster, Paul; García-Pérez, Hilda; Lybecker, Donna; Megdal, Sharon B.; Sanchez, Rosario; Sweedler, Alan; Varady, Robert G.; Zuniga-Teran, Adriana
Abstract: Shortly after being confirmed by the U.S. Senate in 2021, Commissioner Maria Elena Giner called for input into issues of importance to the U.S. Section of the International Boundary and Water Commission (USIBWC). Responding to her call, a group of border scholars committed to producing a white paper entitled "Water Management on the U.S.-Mexico Border: Achieving Water Sustainability and Resilience through Cross-Border Cooperation". This document was presented to Commissioner Giner at the spring 2022 ABS Annual Meeting in Denver, Colorado. This commentary outlines the main ideas and recommendations in this white paper, which are intended to strengthen the USIBWC's ability to respond to the challenges of U.S.-Mexico border water management in the 21st century. The paper recognizes the IBWC's long history of handling binational water issues effectively and its demonstrated capacity to respond and adapt to the border region's changing social, political, and environmental conditions. The commentary is capped with Commissioner Giner's response to the white paper, including her commitment to work with the academic community in both countries in creating an IBWC's binational science advisory group, as recommended in the white paper.